The study of association between the companies market value and the oil and gas reserve value - Abdulrahman, Bazhar; Abdal, Kahi Ilham (International Journal of Scientific Research and Management (IJSRM), 2019)
This research investigates the relationship between oil and gas reserves value and oil and gas company's market value by using samples of oil and gas companies which internationally base from 2007 to 2011. Additionally, in order to find the overall relationship between oil and gas reserves and the company’s market value, this research has found the average value of oil and gas reserves in the year and then used the calculated market value which has been calculated by the researcher (cohort study). To find the individual association between oil and gas reserves value and oil and gas market value, this research has found the correlation by using excel spreadsheet and used the annual amount of oil and gas reserves then multiplied by annual averages of oil and gas prices (panel study). Additionally, in order to find the relationship between oil and gas reserves and company’s market value, this research has found the allocated companies' market value. The overall result of this research shows there is a positive relationship between oil and gas reserves value and oil and gas company's market value. Besides, for the individual relationship between oil and reserves value and oil and gas company's market value, the result was different from company to company and the difference can be there depending on the company reserves amount, companies' strategies toward reserves disclosure and the company size.